Multifocal Discharges and Ictal Correlates - J Gordon Millichap (Pediatric Neurology Briefs)
Continuous EEG/video recordings on 4 children with the interictal EEG pattern of multifocal independent epileptiform discharges (MIED) are reported from the Epilepsy Center, The Johns Hopkins University School of Medicine, Baltimore, MD.